Factores de éxito para la penetración de empresas peruanas y mexicanas al mercado de EE.UU. en el segmento de salsas picantes - Beltran Chavez, Darleni Jessica Tamara (2022)
The hot sauce market has shown great global growth in the last six years. It is estimated that by 2025 it will reach a value of almost USD 6 billion, with a CAGR of 5%. Around the world, North America has the most consumers and the most important hot sauce companies, located in the United States and Mexico. The latter has increased its exports with a CAGR of 8% between the years 2015 and 2020. Their hot sauces are the best known internationally and it is the main supplier to the United States, the largest destination market for hot sauces in the world. On the other hand, Peru has a large catalog of chili peppers, more than 300, but its sauces are not as well known as the ones mentioned above. Within its portfolio, those made from yellow pepper, panca and rocoto stand out. They have also increased their world exports during this period, with almost 6 million dollars exported in 2019 and a CAGR of 5%. However, local manufacturers have shown some problems to position themselves internationally, such as the local supply of chili peppers and the standardization of crops, along with the poor port and logistic infrastructure. Based on the study of success cases, it was identified that the most important factors for the entry of small Peruvian companies to the United States are the alliances with dealers, providing the services of contract manufacturers, and a focus on nostalgic markets, with an emphasis on the Peruvian immigrant population. Conversely, the better positioning of Mexico is due to its proximity to the United States; in addition to having more immigrants there, a longer time to establish their sauces with marketing and gastronomy, and the fact that their chilies are more attractive to the American consumer because of their spiciness.